The Relationship Between Granger Causality Analysis and Indonesian Trade and Economic Growth. - Yuliansyah, Yuliansyah; Gunarto, Toto; Ciptawaty, Ukhti; Ninidien, Qurrota Ayu; Afif, Fadeli Yusuf (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
These findings confirm that the contribution of domestic assets to economic growth is relatively limited, which is in line with the literature that emphasizes the more dominant role of foreign direct investment, household consumption, and fiscal and monetary policies in influencing the Indonesian economy. Second, the causality test on foreign assets also shows similar results, namely that economic growth has not been proven to affect changes in foreign assets, and vice versa. Based on the findings of this study, the recommendation for the government is to implement economic development policies that are more focused on strengthening the domestic foundation, particularly by encouraging productive investment, increasing the competitiveness of the real sector, and strengthening household consumption, which has been proven to be more significant in driving economic growth